Big Data Analysis as a Source of Companies’ Competitive Advantage: A Review - Małgorzata Bartosik-Purgat; Milena Ratajczak-Mrozek (Entrepreneurial Business and Economics Review, 2018)
Objective: The main aim of the article is two-fold: firstly, to indicate the benefits to companies. which stem from the usage of Big Data Analysis (BDA), and secondly to conceptualise main general sources of competitive advantage that BDA affords.